Analysis of Curvature in Fiber Optic Cable for Macrobending-Based Slope Sensor - Mulyanto, Imam (Journal of Technomaterial Physics, 2021)
The analysis of fiber optics for macro bending-based slope sensors using SMF-28 single-mode optical fibers has been successfully conducted. Fiber optics were treated to silicon rubber molding and connected with laser light and power meters to measure the intensity of laser power generated. The working principle was carried out using the macrobending phenomenon on single-mode optical fibers. The intensity of laser light in fiber optic cables decreases in the event of indentation or bending of the fiber optic cable. Power losses resulting from the macrobending process can be seen in the result of the information sensitivity of fiber optics to the change of angle given. From the results of the study, the resulting fiber optic sensitivity value is -0.1534o/dBm. The larger the angle given, the lower the laser intensity received by the power meter.